Clinical assessment and transcriptome analysis of host immune responses in a vaccination-challenge study using a glycoprotein G deletion mutant vaccine strain of infectious laryngotracheitis virus - Gopakumar, Gayathri; Coppo, Mauricio J. C.; Diaz-Méndez, Andrés; Hartley, Carol A.; Devlin, Joanne M. (Frontiers in Immunology, 2025)
A glycoprotein-G-deleted live-attenuated vaccine strain of the infectious laryngotracheitis virus (ILTV), ΔgG-ILTV, is safe and efficacious against ILTV challenge. In the current study, the transcriptome of peripheral blood mononuclear cells (PBMCs) of the ΔgG-ILTV-vaccinated group of specific-pathogen-free chickens were compared to those of the nonvaccinated group at 7 days post-vaccination. Tracheal transcriptomes after challenge with virulent ILTV were compared between groups of the non-vaccinated-challenged and the vaccinated-challenged as well as the non-vaccinated-challenged and the uninfected chickens at 4 to 5 days post-challenge. The clinical outcomes after challenge between these groups were also evaluated. Significant differences were observed in the tracheal transcriptome of the non-vaccinated-challenged birds compared to the other two groups. Enriched gene ontologies and pathways that indicated heightened immune responses and impairments to ciliary and neuronal functions, cell junction components, and potential damages to cartilaginous and extracellular components in the trachea of the non-vaccinated-challenged birds were consistent with their severe tracheal pathology compared to the other two groups. On the contrary, the absence of any difference in the tracheal transcriptome between the vaccinated-challenged and the uninfected birds were reflected by the preservation of tracheal mucosal integrity in both groups and mild infiltration of leukocytes in the vaccinated-challenged birds. The results from this study demonstrated that vaccination with ΔgG-ILTV prevented the changes in tracheal transcriptome induced during ILTV challenge, resulting in clinical protection. Additionally, these results also provide insights into the molecular mechanisms underlying the tracheal pathology induced by ILTV infection.